2008
DOI: 10.2135/cropsci2008.01.0047
|View full text |Cite
|
Sign up to set email alerts
|

Safflower Winter Survival and Selection Response Relates to Fall Growth Morphology and Acclimation Capacity

Abstract: Fall‐planted safflower (Carthamus tinctorius L.) offers potentially higher yield than spring‐sown types. Yet winter survival in relation to fall growth and physiological aspects of acclimation has not been determined. Our objectives were (i) to determine the relationship between fall growth and winter survival in safflower, (ii) to assess if selection improved winter survival, and (iii) to determine if water relations and membrane leakage distinguished safflower varying in winter survival. Fall growth, leaf wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Winter types PI 651878, PI 651879, and PI 651880 were developed as outlined by Johnson and Li (2008b) at the USDA-ARS Western Regional Plant Introduction Station, Pullman, WA, and released by USDA-ARS in 2007. An additional winter type, PI 405985 (Auld et al, 1983;Johnson et al, 2006;Johnson and Li, 2008a) from Iran, was used in mass selection under winter conditions as described by Johnson and Li (2008b) and documented in the Germplasm Resources Information Network as W6 39446.…”
Section: Germplasmmentioning
confidence: 99%
See 3 more Smart Citations
“…Winter types PI 651878, PI 651879, and PI 651880 were developed as outlined by Johnson and Li (2008b) at the USDA-ARS Western Regional Plant Introduction Station, Pullman, WA, and released by USDA-ARS in 2007. An additional winter type, PI 405985 (Auld et al, 1983;Johnson et al, 2006;Johnson and Li, 2008a) from Iran, was used in mass selection under winter conditions as described by Johnson and Li (2008b) and documented in the Germplasm Resources Information Network as W6 39446.…”
Section: Germplasmmentioning
confidence: 99%
“…As a result, winter survival has been associated with a long rosette period (Yazdi-Samadi and Zali, 1979), and genotypes with a prolonged rosette period usually have increased cold tolerance and are considered winter types (Ghanavati and Knowles, 1977). Johnson et al (2006) and Johnson and Li (2008a) showed that winter survival was related to low plant height or prostate habit associated with the rosette stage in the fall, but genetic variation in physiological acclimation capacity was also critical to improve winter survival. Johnson et al (2006) and Johnson and Li (2008a) showed that winter survival was related to low plant height or prostate habit associated with the rosette stage in the fall, but genetic variation in physiological acclimation capacity was also critical to improve winter survival.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two safflower varieties were used in this study: ‘winter hardy’ C311, known to survive extended cold periods (including overwintering under snow) and ‘spring’ S317, which is a widely grown commercial cultivar ( Wood et al, 2018 ). C311 was sourced from US Department of Agriculture Genetic Resources Information Network (PlantID WSRC03, Johnson and Dajue, 2008 ). Prior to more detailed analysis of flowering time in growth cabinets, S317 and C311 were cultivated in parallel in a small experimental plot at CSIRO Black Mountain site (alluvial soil) in late spring.…”
Section: Methodsmentioning
confidence: 99%